The reverse Napoleon effect: The brand appreciation of looking up by tall people - Ulrich R. Orth; Casparus J. A. Machiels; Gregory M. Rose (Psychology & Marketing, 2020)
Integrating the embodied cognition framework with research on the self, this study shows that head canting (the vertical tilt of the head to look up vs. down) interacts with a viewer's physical height to influence perceived brand power and behavioral intentions. Three studies use a variety of brand cues in both laboratory and field contexts to test the effect of head canting on brand power evaluations, the role of a person's physical height as a moderator and boundary condition, and the mediating role of consumer–brand identification. Study 1, an experiment, showed that tall, but not short individuals, evaluate a brand as more powerful when looking up (rather than down) at a brand story from a standing position, with differences in brand power impacting brand attitudes and choice. Study 2 replicates these findings with 30 brands, consumers positioned in a seated position, and brand logos. Both studies rule out the construal level as a process mediator. Study 3 further examines the process and demonstrates that the interaction of head canting with a person's height impacts consumer–brand identification, which mediates brand evaluations. These findings add a brand management and physical-self perspective to previous embodiment research by specifically examining the effects of sensorimotor experiences.
Keywords: 650; brand power; construal level; embodiment; physical height; sensorimotor experience